ANALISIS KEMAMPUAN BERPIKIR ALJABAR SISWA DALAM MODEL PEMBELAJARAN LEARNING CYCLE 5E - Uzliva Silma (Jurnal Pembelajaran Matematika, 2018)
understanding the concept of algebra. So, an innovative learning model is needed to make students more active in understanding the concept. One of the innovative learning models is Learning Cycle 5E. The objective of this study is (1) to find out whether the algebra thinking ability of class VII in the Learning Cycle 5 achieves classical completeness; (2) to describe the algebra thinking ability of class VII in Learning Cycle 5E. The research method is mixed methods. The populations in this study are seventh grade students consisting of 281 students. The sample in this study is students of class VII F consisting of 36 students. Simple random is chosen as sampling technique. Quantitative data is collected using tests and it is analyzed using z test. The subjects in this study are 9 students. The variable is algebra thinking ability. In determining the subject, the researcher employs purposive sampling technique. Meanwhile, qualitative data analysis is analysis of interview data. The results show that (1) algebra thinking ability of class VII in 5E Learning Cycle achieves classical completeness of 83.33%; (2) the results of algebra thinking ability tasks are: (a) students in high-level algebra thinking ability have high generational, transformational, and global meta abilities; (b) students in middle algebra thinking ability have high generational and transformational abilities, and moderate global meta abilities; and (c) students in low-level algebra thinking ability have moderate generational and transformational abilities, and they have low global meta abilities.Keywords: Algebra Thinking Ability, 5E Learning Cycle.